Yurisdiksi Kriminal Terhadap Black Flight Di Ruang Udara Wilayah Indonesia - Candra Ulfatun Nisa; Hari Sutra Disemadi (Faculty of Law, Universitas Pattimura, 2020)
The state in its capacity as one of the subjects of international law, has the rights and obligations associated with sovereignty. The state is free and independent to exercise its sovereignty rights in full but also has an obligation to pay attention to its limits in not exercising its sovereignty in the territory of other countries. Regarding the sovereignty of the territory of the Republic of Indonesia, even though it has clearly established its boundaries and has been recognized by international law, violations of sovereignty territories often occur that are not intentional or intentional to achieve certain goals. One of them is a violation of the sovereignty of Indonesian airspace, namely black flight. The method of research using the normative juridical approach, with descriptive research specifications. The results of this study are that Indonesia's sovereignty over its national airspace boundaries is full, exclusive and fully closed to foreign aircraft or aircraft belonging to other countries. With regard to black flight, Indonesia by TNI-AU carries out criminal jurisdiction with a lighter action preceded in the form of a warning to get out and immediately leave the Indonesian airspace, to the more severe act of forcing a landing.